A mathematical modeling of crosslinking between components of a polymer composition - Pasichnyk, Maria; Kucher, Elena (Eastern-European Journal of Enterprise Technologies, 2016)
The paper presents a method of mathematical modeling as a most promising way to determine the structural parameters of the polymer network. In polymer systems, modeling is developed in different directions, although its capacity in studying the processes of crosslinking polymer networks is not used to full extent. We used the interpolation method to build the 4th-degree Lagrange interpolation polynomial that allowed determining the optimal amount of a crosslinking agent. A three-factor model of crosslinking polymeric components was constructed with the use of the multiple regression equation. The model showed the main concentration of the composition components that would ensure the degree of crosslinking at an optimal level of 25–50 %. The research resulted in designing four polymer compositions. It was found that films with a crosslinking degree of 20–25 % have the relative elongation rate of 682 % and the breaking load value of 18 H. The findings of the physical and mechanical research of films were used to build the deformation and strength curves. It was determined that when the optimal degree of crosslinking is 20–21 %, urethane-based polymer compositions (PC-2 and PC-3) have a relative elongation rate of 300–700 % and the breaking load of 40–50 MPa, which proves the dependence of the deformation the strength characteristics of films on the degree of crosslinking between the components. The paper presents charts of the degree of crosslinking dependence on the component concentration. The constructed graphs of the response surface allow selecting the required concentrations of ingredients for obtaining polymer films with a desired crosslink density. The calculated structures of networks have proved the relevance of the suggested mathematical models (the coefficient of determination R2 equaling 0.92 and 0.98).